Configuração das práticas de saúde entre médicos e enfermeiros no ambiente hospitalar, na perspectiva das relações de poder - Tauana Wazir Mattar e Silva (2018)
The hospital environment is a symbol of the social power of the medical profession, favoring the visibility of this professional as a central actor of care. The growing administrative professionalization of hospitals requires that their employees, including doctors, commit themselves to bureaucratic activities, which are often mediated by nurses. Thus, in spite of the strong valorization of the physician-centered model in care, it is observed that the nurses have achieved visibility by the managerial practices, which can generate tensions in the professional relations. This new hospital conformation reconfigures power relations. The power circulates constantly, according to the composition of forces formed from knowledge and practices by the Foucauldian referential. In professional relations, those who hold the greatest knowledge assume a privileged position in the relations of power. With the objective of analyzing how power relations are constituted in the knowledge and daily practices of physicians and nurses in the hospital environment, a qualitative research was developed in the poststructuralist perspective, based on the theoretical and methodological framework of the French philosopher Michael Foucault. The study scenario was the Intensive Care Center of a large general philanthropic hospital, located in the city of Belo Horizonte, capital of Minas Gerais, Brazil. In the Intensive Care Center, the field was observed and interviews were conducted with a semistructured script to 08 doctors and 12 nurses. From the analysis of the constituted discourses, three main empirical categories were identified: Professional identity: recognition of self in the profession, Discipline: individualizing attitudes or collective need? and Power: constitution knowledge of everyday practices. The evaluation of the data allowed us to reflect that the configuration of health practices among physicians and nurses in the hospital environment pervades socioeconomic, historical, cultural and gender issues. Such questions influence the subject's identity formation, the desire for visibility, its acceptability to discipline and the search for the movement of power through knowledge. It was noticed that the relationships between doctors and nurses are eminently problematic, as well as tension, power struggle among the doctors themselves, and lack of unity among the nurses, who are alienated to the direct care of the patient. The speeches show that the medical team in general, does not have intimacy with the institutional norms, being, therefore, the nurses the main guides of this process. However, few nurses have made their safety clear about the technical knowledge required by the profession, especially when communicating hemodynamic changes to physicians, performing invasive procedures or even assisting them. This study allows the encouragement of other research that associated with it may contribute to better health practices among physicians and nurses working in intensive care units